Maintaining good mental health in people with inflammatory arthritis: a qualitative study of patients’ perspectives - Signe Marie Abild; Julie Midtgaard; Annika Nordkamp; Annette de Thurah; Sofie Bech Vestergaard; Bente Glintborg; Mette Aadahl; Pernille Fevejle Cromhout; Lene Lau; Connie Yilmaz; Bente Appel Esbensen (International Journal of Qualitative Studies on Health & Well-Being)
Purpose It is well-documented that people with inflammatory arthritis (IA) exhibit a high prevalence of symptoms related to anxiety and depression. Less is known about what contributes to good mental health in people with IA. Therefore, this study aims to explore how some patients maintain good mental health despite living with IA. Methods Explorative qualitative interview study (one focus group, 12 individual interviews, n = 18) utilizing purposeful sampling. All interviews were audiotaped, transcribed, and managed using NVivo14 and employed a reflexive thematical analysis approach. Results We identified four main themes: 1) Assisted by a positive outlook on life—how participants’ inherent positivity helped them cope with arthritis; 2) Moving towards acceptance of life with arthritis—how participants embraced the reality of living with IA; 3) Counteracting letting arthritis dictate one’s life how the participants structured their lives in terms of physical activity and social connections; and 4) Taking responsibility for the trajectory—how the participants were mindful of their bodies and took the initiative to explore new treatments. Conclusion People living with IA maintain good mental health by engaging in structured physical activity, fostering social connections, and cultivating a positive outlook on life. These insights can inform the development of future treatment and support strategies.